IMPROVING ORGANIZATIONAL WORK PROCESS OF LAND REGISTRATION BASED ON 3D CADASTRE AND CADASTRE 2014 CONCEPTS (Case Study Apartment Unit Registration) - Suhattanto, M Arif (BHUMI: Jurnal Agraria dan Pertanahan, 2018)
The need for land always increases but the area of land never increases. This makes people to use the land effectively. The use of traditional cadastre; the use of 2 dimensional cadastral concept, is no longer able to fulfill the complete cadastral needs. Having experiments on applying the 2 dimensional land registration, knowledge on 2014 cadastral concepts and 3 dimensional cadastral concepts, the development of the ongoing organization’s work process is badly required. The paper is aimed at explaining how to design the process of land registration in applying the 3 D cadastral and 2014 cadastral concepts using a modeling process. The result of the process is the new diagram showing the change of the organization; both inside and outside. However, due to the complexity of the 3 D cadastral concept, the discussion is limited to the apartment units in Indonesia. Keywords: 3D cadastre, 2014 cadastre, modeling.